Genetic association of productive traits, carcass measurements and age at first calving in the genetic evaluation of the Nellore breed - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C. I. Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
The aim was to evaluate the genetic association between sexual precocity and productive performance in Nellore cattle. Records of standardized body weights at 120 (W120), 210 (W210), 365 (W365), and 450 (W450) days of age, Longissimus Muscle Area (LMA), backfat thickness (BFT), and age at first calving (AFC) were used. The mixed linear model included the fixed effects of contemporary groups (composed of herd, year, and season of birth, as well as the animal’s sex), in addition to the random effects of direct additive genetic, maternal genetic (for W120 and W210), and maternal permanent environment. The variance components were estimated by the restricted maximum likelihood method. The obtained direct heritability estimates were 0.45, 0.49, 0.42, 0.40, 0.33, 0.19, and 0.08 for W120, W210, W365, W450, LMA, BFT, and AFC, respectively. The Spearman correlations of the animals’ breeding values between the weight development estimates were of a high order, and for the traits of backfat thickness and age at first calving, it was 0.27, indicating a relationship at older ages with the onset of the acceleration of adipogenesis. The genetic gain obtained in AFC (0.48 days) with the correlated response related to LMA and BFT was − 0.05 and − 0.19 days, respectively. The genetic correlations obtained between AFC and the weight development traits were positive, however negative with the carcass-associated traits, indicating that the offspring are reproductively precocious, yet lighter and with a greater finish of subcutaneous fat.

Reaction norm models for the evaluation of reproductive and productive performance in Nellore cattle - F. L. Menezes; S. I. Araújo; R. B. Lobo; L. R. M. Nakabashi; F. Baldi; N. L. Pavan; G. C.I Seidel; C. V. Araújo (Tropical Animal Health and Production, 2026)
This study evaluated genotype × environment interactions (G×E) in Nellore cattle for growth, reproductive, and carcass traits using reaction norm models. We analyzed the records of body weight and scrotal circumference at 12 and 18 months. (W365, W450, SC365, SC450), as well as loin eye area (LEA) and subcutaneous fat thickness (SFT), from herds across different Brazilian states were analyzed. A hierarchical one-step reaction norm model was applied, including fixed effects of contemporary groups (herd, year and season of birth, and sex), cow age at calving as a covariate, and random effects for additive genetics, permanent environment, and residuals. Bayesian inference with Gibbs sampling was used to estimate posterior distributions.Sires were classified according to environmental sensitivity into four categories: extremely robust, robust, plastic, and extremely plastic. For most traits, over 90% of sires were classified as robust or extremely robust, indicating stability of ranking across environments. Exceptions were observed for SFT and SC365, where lower correlations between extreme environmental gradients suggested G×E effects. Heritability estimates ranged from 0.07 to 0.32 for body weights and reached up to 0.76 for fat thickness, with higher values observed under more favorable environmental conditions. .These findings underscore the utility of reaction norm models for identifying environmentally robust sires under the variability of tropical production systems, thereby supporting more accurate and efficient selection decisions in genetic improvement programs.

An actor-centered, scalable land system typology for addressing biodiversity loss in the world’s tropical dry woodlands - Marie Pratzer; Patrick Meyfroidt; Marina Antongiovanni; Roxana Aragon; Germán Baldi; Stasiek Czaplicki Cabezas; Cristina A. de la Vega-Leinert; Shalini Dhyani; Jean-Christophe Diepart; Pedro David Fernandez; Stephen T. Garnett; Gregorio I. Gavier Pizarro; et al. (Global Environmental Change, 2024)

Pesticide exposure in greenspaces: Comparing field measurement of dermal contamination with values predicted by registration models - L. de Graaf; M. Bresson; M. Boulanger; M. Bureau; Y. Lecluse; P. Lebailly; I. Baldi (Science of The Total Environment, 2024)

CEC06-03: Documenting pesticide exposures from field studies: what is known and why we should know more - I. Baldi (Toxicology Letters, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global patterns of rainfall partitioning by invasive woody plants - Juan I. Whitworth‐Hulse; Patricio N. Magliano; Sebastián R. Zeballos; Sebastián Aguiar; Germán Baldi (Global Ecology and Biogeography, 2021)
Aim Invasive species have the potential to alter hydrological processes by changing the local water balance. However, general patterns of how rainfall is partitioned into interception, throughfall and stemflow for invasive species worldwide have been seldom explored. We (a) describe the percentage of interception, throughfall and stemflow for invasive woody plant species; (b) analyse the influence of morphological attributes (i.e. life‐form, bark roughness, leaf type, leaf phenology and leaf area index) of invasive species on rainfall partitioning; and (c) compare the rainfall partitioning fluxes for co‐occurring invasive and native species, testing whether the variation in these fluxes depends on water availability of the study location. Location Global. Time period Present. Major taxa studied Plants. Methods We compiled data of 100 studies that assessed rainfall partitioning by invasive species ( n = 67) and registered their morphological attributes. By means of a meta‐analysis we compared the rainfall partitioning by native and invasive species ( n = 47 comparisons) and assessed how their fluxes were affected by water availability. Results Interception, throughfall and stemflow ranged from 1.6–59.5, 39.1–92.7 and 0.1–31.6% of total rainfall, respectively. The bark roughness and leaf type were the most important attributes driving rainfall partitioning fluxes. While rough‐barked species constrain rainfall inputs by promoting higher losses due to interception, smooth‐barked species with broad leaves enhance the amount of rainwater reaching the soil by maximizing stemflow. For pairwise comparisons, invasive species have higher stemflow values than native species for both drylands and humid areas, and higher throughfall in drylands, but less in humid areas. Main conclusions Our findings suggest that specific morphological attributes of invasive species determine higher localized water inputs, which may represent an ecohydrological advantage, particularly in water‐limited ecosystems. These insights also suggest that the ecological role of stemflow, throughfall and interception should be considered in future plant invasions research.

Modeling coseismic displacements resulting from SAR interferometry and GPS measurements during the 1997 Umbria-Marche seismic sequence - S. Salvi; S. Stramondo; M. Cocco; M. Tesauro; I. Hunstad; M. Anzidei; P. Briole; P. Baldi; E. Sansosti; G. Fornaro; R. Lanari; F. Doumaz; et al. (Journal of Seismology, 2000)